Percutaneous release of trigger finger without local anaesthesia as an outpatient procedure - Kumar Malviya, Vikas; Kripal Soni, Ram (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2019)
Background: Stenosing tenosynovitis or trigger finger frequently involves the thumb and ring fingers of the dominant hand and more commonly seen in adult female population, in their 5th and 6th decades of life. Method: In this study, 18-gauge needle was used for the percutaneous release of trigger finger without any local anaesthesia in 12 patients with prior consent. Results: Highest numbers of patients were in 41-60 years age group (66.7%). 3 patients (25%) belong to 20-41 years age group. Only 1 patient (8.3%) of age group 61-80 was affected by trigger finger. 7 Patients (58.3%) were females and 5 patients (41.6%) were males. The most commonly affected finger was the ring (58.3%) followed by the middle (33.3%) and index (8.3%). Right hand and left hand was affected side in 8 (66.6%) and 4 (33.3%) patients respectively. According to greens classification, Grade II patients were 50%, grade III 41.6% and grade IV 8.3%. Average duration of the procedure was 5-7 minutes. There was no evidence of complications. 4 patients experienced mild postoperative pain. In one patient the procedure has to be abandoned as patient could not tolerate the pain. Conclusion: As we do not use local anaesthesia localization of A 1 pulley in trigger finger is much easier for percutaneous release. Therefore, the procedure is more effective and time saving as well.